Development of Web Application to Support Special Investigations - Sangphon , Puwanai; Jirapanthong, Waraporn (JOURNAL OF INFORMATION SCIENCE AND TECHNOLOGY, 2024)
This article introduces the development of a web application designed and developed to support the investigation of special cases, particularly those with a high number of victims. The users are categorized into three groups: the general public, who are victims; special case investigators; and administrators. The system is equipped with the capability to manage case data and investigators, as well as to register victims through online forms. Additionally, it can record testimonies, generate reports, and compile relevant documents efficiently. The system also provides efficient statistical analysis and various reports.